Longitudinal changes in factors affecting postoperative patient satisfaction after robot-assisted radical prostatectomy: an assessment using a patient-reported questionnaire - Soichiro Ogawa; Kei Yaginuma; Yuki Harigane; Shunta Makabe; Hitomi Imai; Satoru Meguro; Ryo Tanji; Akifumi Onagi; Ruriko Honda-Takinami; Kanako Matsuoka; Seiji Hoshi; Junya Hata; et al. (BMC Urology)
Abstract Background Long-term survival can be achieved in patients with localized prostate cancer (PCa). Therefore, maintenance of postoperative quality of life (QOL) and treatment satisfaction are important. Although longitudinal changes in disease-specific QOL are reported, there are few studies investigating which factors longitudinally affect treatment satisfaction in patients who undergo robot-assisted radical prostatectomy (RARP). Therefore, we examined the factors associated with treatment satisfaction over the first 12 months postoperatively based on an assessment using a patient-reported questionnaire. Methods Of the 612 consecutive patients who underwent RARP, 408 patients were enrolled in this study and divided into a satisfied group and a non-satisfied group at every evaluation timepoint. Multivariate logistic regression analysis was conducted to clarify factors affecting the postoperative treatment satisfaction between the two groups. Results Multivariate logistic regression analysis revealed that factors relating to treatment satisfaction had longitudinally changed. Urinary bother (UB) (odds ratio (OR) = 1.023; p = 0.008), and sexual function (SF) (OR = 0.941; p = 0.004) were the significant factors associated with treatment satisfaction at 1 month postoperatively; UB (OR = 1.040; p = 0.001) and sexual bother (SB) (OR = 1.019; p < 0.001) at 3 months; urinary function (UF) (OR = 1.027; p = 0.008), UB (OR = 1.035; p = 0.011), SB (OR = 1.013; p = 0.009), and hormonal bother (HB) (OR = 1.065; p = 0.023) at 6 months; UF (OR = 1.026; p = 0.008), UB (OR = 1.030; p = 0.029), and SB (OR = 1.014; p = 0.004) at 9 months; UF (OR = 1.024; p = 0.002) at 12 months. Conclusions Treatment satisfaction in patients who underwent RARP changed over time. Our results suggest that giving sufficient information before treatment choice is both important and useful for patients’ decision-making, leading to improved patient QOL.